ECOLOGY OF CHIROPTERA BATS IN ALTAI-SAYAN REGION OF SOUTHERN SIBERIA - A. V. Zhigalin; A. A. Gadzhiev; M. G. Daudova; N. G. Salimkhanov; A. M. Shestopalov (Юг России: экология, развитие, 2019)
Aim. The aim of this work is to summarize the available data on zoogeographic analysis and fauna of the bats of the Altai-Sayan region.Discussion. The chiropterofauna of the AltaiSayan highlands includes the representatives of 13 species. The obtained data on the distribution of bats in the region made it possible for the first time to carry out a zoogeographic analysis of the chiropterofauna of the Altai-Sayan highland. The faunal complex of bats in the study area and adjacent territories is represented by boreal, European and Central Asian species. The cluster analysis by Jaccard coefficient allowed us to distinguish two main chiropterological complexes: Altai-Sayan and Ubsunur. Our boundary between these complexes coincides or is close to the biogeographic boundaries drawn for various groups of vertebrates and invertebrates, as well as plants.Conclusion. Altai-Sayan territory is inhabited by 13 bat species of six genera belonging to Vespertilionidae family. The most common species are the following: eastern water bat – Myotis petax Hollister, 1912; Siberian bat – Myotis sibiricus Kastschenko, 1905; Ikonnikov's bat – Myotis ikonnikov Ognev, 1912; Northern bat – Eptesicus nilssonii Keyserling, Blasius, 1839; Parti-coloured bat – Vespertilio murinus Linnaeus, 1758; Ognev's long-eared bat – Plecotus ognevi Kishida, 1927. In the fauna of the region, the boundary between two chiropterological complexes (Altai-Sayan and Ubsunur) runs through Kurtushibinsk-Usinsk province.